Operation of High-Speed Switched Reluctance Machines with a Non-Uniform Air Gap - Ryszard Palka (Energies)
This paper deals with an analysis of the operation of switched reluctance machines with a non-uniform air gap. The main focus was on the analysis of the performance of machines with a linearly decreasing air gap. Intensive field calculations made it possible to provide their accurate characteristics, which were then used in simulations of various dynamic states. On this basis, the advantages and disadvantages of machines with a non-uniform air gap were finally discussed from the point of view of applications in efficient high-speed drive systems.